Paradigm Shift in Higher Education through ICT: Conventional to MOOCs -A Case Study of Dibrugarh University - Mahanta, Shrutidhara (Indian Journal of Educational Technology, 2020)
The purpose of this paper is to examine the role of ICT services in the higher education sector both in the ODL system as well as in conventional system of education. Integration of ICT services in ODL makes it wide spread, accessible to remote, accessible to all. These are found to be useful for the distance learners of Dibrugarh University (DU). Moreover, the benefits of ICT integrated education can also be achieved by the conventional students, if convergence between the two systems is established by allowing the students to earn few credits under MOOCs in CBCS. DU has already made progress in this front and due to an awareness drive a significant number of students got enrolled to various courses under SWAYAM. The researcher studied few of these initiatives taken by DU to cope up with the global trend of ICT integrated HE. Researchers, academicians, administrators of the state and other regions of the country will be benefited from the findings.